2016
DOI: 10.1542/hpeds.2015-0224
|View full text |Cite
|
Sign up to set email alerts
|

Communication and Shared Understanding Between Parents and Resident-Physicians at Night

Abstract: BACKGROUND AND OBJECTIVE Communication breakdowns between members of the health care team compromise patient safety and experience. Communication breakdowns with parents, an important but often overlooked part of the health care team, are understudied. Parents may play a particularly important role in nighttime care given decreased staffing and inadequate transitions of care at night. We studied communication breakdowns evidenced by lack of shared understanding between parents and night-team residents about th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 44 publications
1
10
0
Order By: Relevance
“…We previously found that parent-provider communication breakdowns evidenced by lack of shared understanding about inpatient care plans occurred in 45.1% of parent-resident dyads. 25 We also found that quality of parent-provider nighttime communication was associated with overall hospital experience. 10 We additionally found that parents provided unique information about hospital safety events, particularly communication-related ones.…”
mentioning
confidence: 60%
See 1 more Smart Citation
“…We previously found that parent-provider communication breakdowns evidenced by lack of shared understanding about inpatient care plans occurred in 45.1% of parent-resident dyads. 25 We also found that quality of parent-provider nighttime communication was associated with overall hospital experience. 10 We additionally found that parents provided unique information about hospital safety events, particularly communication-related ones.…”
mentioning
confidence: 60%
“…In a previous study in the same units, we found that 73.1% of providers reported they shared an understanding with parents about the care plan; however, when objectively rated, only 54.9% of provider-parent dyads were rated as having a shared understanding. 25 Additionally, multiple caregivers who do not communicate fully with one another may be present during the hospitalization.…”
Section: Discussionmentioning
confidence: 99%
“…Knowing to look for these signs and symptoms as part of a contingency plan have been highlighted as an essential piece of the hospital-tohome transition. 1 they are often unaware of signs to look out for while their children are hospitalized, 97 providing further evidence that families need additional education in this area.…”
Section: Discussionmentioning
confidence: 99%
“…By increasing patient access to health information, inpatient portals have the potential to enhance patient recognition of their providers and knowledge of their care plan, an area ripe for improvement. 23,24 Information made available to patients through inpatient portals may also augment face-to-face communication with providers. 6 For example, patient-provider shared decision-making during patient-centered rounds may be improved if test results were available to patients through inpatient portals beforehand.…”
Section: Poised To Support Engagementmentioning
confidence: 99%